The motivation of subcontracted workers: a never-ending paradox (2019)
Certain considerations come about the subcontracted workers motivation when the Strategic Human Resource Management is used as a point of reference for diverse analysis. This article shows two faces of Human Resource Management. On one hand, the article indicates how important worker motivation has been for Human Resource Management and its direct association with worker productivity and efficacy. On the other hand, it points out the increasing importance that subcontracting has had as an alternative that allows companies the flexibilization and minimization of labor costs. Even though a structural contradiction comes up in this context, subcontracting seems to strive for feelings of affiliation and pride of belonging which are key elements to motivate the personnel. Apart from the literature review, the study was based on an ethnographic methodology of executives, contractors and subcontracted workers; and the results aim to contribute to streams of Organizational Theory and Human Resource Management.